Zebrafish Foxc1a controls ventricular chamber maturation by directly regulating wwtr1 and nkx2.5 expression. (June 2022) - He, Luqingqing; Zhang, Qinxin; Jiang, Dongya; Zhang, Yunfeng; Wei, Yuxuan; Yang, Yuxi; Li, Nan; Wang, Shuang; Yue, Yunyun; Zhao, Qingshun
Abstract: Chamber maturation is a significant process in cardiac development. Disorders of this crucial process lead to a range of congenital heart defects. Foxc1a is a critical transcription factor reported to regulate the specification of cardiac progenitor cells. However, little is known about the role of Foxc1a in modulating chamber maturation. Previously, we reported that foxc1a -null zebrafish embryos exhibit disrupted heart structures and functions. In this study, we observe that ventricle structure and cardiomyocyte proliferation are abolished during chamber maturation in foxc1a -null zebrafish embryos. To observe the endogenous localization of Foxc1a in the hearts of living embryos, we insert e yfp at the foxc1a genomic locus using TALEN. Analysis of the knockin zebrafish show that foxc1a is widely expressed in ventricular cardiomyocytes during chamber development. Cardiac RNA sequencing analysis reveals the downregulated expression of the Hippo signaling effector wwtr1 . Dual-luciferase and chromatin immunoprecipitation assays reveal that Foxc1a can bind directly to three sites in the wwtr1 promoter region. Furthermore, wwtr1 mRNA overexpression is sufficient to reverse the ventricle defects during chamber maturation. Conditional overexpression of nkx2.5 also partially rescues the ventricular defects during chamber development. These findings demonstrate that wwtr1 and nkx2.5 are direct targets of Foxc1a during ventricular chamber maturation.